Sociolinguistic analysis of code mixing and code switching in Nessie Judge and Cinta Laura's “Glitch in the Matrix” YouTube video - Qutratu'ain, Dita Shafa; Yuliano, Siti Annisa; Ersa, Moch.; Degaf, Agwin (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2024)
This research explores the use of code-mixing and code-switching in the YouTube collaboration video